2012
DOI: 10.1007/s10658-012-9958-8
|View full text |Cite
|
Sign up to set email alerts
|

Fusarium temperatum, a mycotoxin-producing pathogen of maize

Abstract: In a recent study, a population of Fusarium strains isolated from maize in Belgium was described as a new species, F. temperatum, that is morphologically similar and phylogenetically closely related to F. subglutinans, a species in the American clade of the Gibberella fujikuroi species complex. In fields, the F. temperatum:F. subglutinans ratio was very high, suggesting that F. temperatum outcompetes its sister species F. subglutinans. This raised the question whether this novel species contributes to the fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
43
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 35 publications
10
43
1
2
Order By: Relevance
“…It is controversial whether F. temperatum is a fumonisin producer. In Belgium, Scauflaire et al (2012) found that one out of eleven isolates produced low levels of FB 1 . In Argentina, higher ratio of F. temperatum isolates (10/38) were identified as low fumonisin producers (max.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is controversial whether F. temperatum is a fumonisin producer. In Belgium, Scauflaire et al (2012) found that one out of eleven isolates produced low levels of FB 1 . In Argentina, higher ratio of F. temperatum isolates (10/38) were identified as low fumonisin producers (max.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenicity of Fusarium isolates on maize stalks was tested by toothpick inoculation as described previously (Scauflaire et al, 2012). Zhengdan 958, the most widely grown maize variety in China, was planted in three different blocks.…”
Section: Pathogenicity Testmentioning
confidence: 99%
See 1 more Smart Citation
“…temperatum F. subglutianans (Scauflaire , 2012), (Varela , 2013), (Wang , 2014) (Fumero , 2015) . , , .…”
Section: Ef1aunclassified
“…, , . fumonisin, moniliformin, beauvericin, fusaproliferin, fusaric acid (Lew , 1996;Scauflaire , 2012).…”
Section: Ef1aunclassified